Turning points during the life of student project teams: A qualitative study - Elisabeth Raes; Filip Dochy; Eva Kyndt (EARLI, 2015)
In this qualitative study a more flexible alternative of conceptualising changes over time in teams is tested within student project teams. The conceptualisation uses turning points during the lifespan of a team to outline team development, based on work by Erbert, Mearns, & Dena (2005). Turning points are moments that made a significant difference during the course of the collaboration as a team. In this study, they are tracked by means of team interviews and reflection papers of team members. A method of coding was created to collect all information about the turning points, their causes and consequences. By means of a thorough analysis of these coded data an overview of their nature and their effects on the rest of the team process as perceived by the team members themselves is provided. Results show that the development paths of the three teams were differentiated in terms of turning points that occurred and, especially, in the order in which the turning points occurred. However four types of turning points (two at the task level en two at the interpersonal level) were remarkable due to their occurrence in all three project teams.